1999
DOI: 10.1097/00054725-199908000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Presenting Symptoms and Diagnostic Lag in Children with Inflammatory Bowel Disease

Abstract: Presenting symptoms and their duration may affect the time that elapses prior to definitive diagnosis of inflammatory bowel disease (IBD). This study was undertaken to determine the mean duration of presenting symptoms and diagnostic lag in children with IBD. The medical records of all patients less than 19 years of age diagnosed with IBD at the pediatric gastroenterology clinic of Children's Hospital of Wisconsin between 1990-1995 were reviewed. The age at diagnosis, gender, presenting symptoms and duration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 10 publications
5
22
0
Order By: Relevance
“…Previous studies reported mean ages at diagnosis ranging from 9 to 13 years old for children with CD and UC, whereas children with IC were slightly younger (7 to 12 years old) when diagnosed 9, 16 . In our cohort, AA children were more likely to be >12 years old when diagnosed with IBD than the non-AA children.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies reported mean ages at diagnosis ranging from 9 to 13 years old for children with CD and UC, whereas children with IC were slightly younger (7 to 12 years old) when diagnosed 9, 16 . In our cohort, AA children were more likely to be >12 years old when diagnosed with IBD than the non-AA children.…”
Section: Discussionmentioning
confidence: 94%
“…Using dates of diagnosis in conjunction with duration of symptoms, estimated ages of IBD symptom onset in recent pediatric investigations ranged from 6 to 12 years old, irrespective of race/ethnicity 16, 18 . Among AA in our study population, symptoms of CD and UC, as well as all IBD classifications combined, appeared to begin more frequently in the teenage years (>12 years old).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is particularly challenging in children, for whom presenting symptoms may vary widely and may only consist of subtle extra-intestinal manifestations [4]. This in turn leads to a typical delay in the diagnosis of pediatric IBD, ranging from 4 weeks in severe colitis [5] to 6–7 months in milder disease [4].…”
Section: Introductionmentioning
confidence: 99%
“…This in turn leads to a typical delay in the diagnosis of pediatric IBD, ranging from 4 weeks in severe colitis [5] to 6–7 months in milder disease [4]. Reducing this diagnostic delay is important, since a long period of unmanaged symptoms can significantly impact growth [5] and early treatment is essential to preserving long-term quality of life [6].…”
Section: Introductionmentioning
confidence: 99%
“…Children with IBD often experience pediatric-specific complications including growth failure and pubertal delay. The diagnosis of IBD in children is commonly delayed (2, 3), which can exacerbate these complications; the majority of children with IBD have growth failure at the time of diagnosis (4). Current therapeutic interventions are unable to permanently ameliorate symptoms and many are associated with potentially severe side effects.…”
Section: Introductionmentioning
confidence: 99%